English Result. Elementary Teacher's Book - McDonald A. Annie (Oxford, Oxford University Press, 2012)
Help students learn the language they need and put it into practice immediately with English Result. Teacher's Book with DVD Pack includes: Interleaved Student's Book pages Full notes, including warmers, extra activities, and culture notes Checklists for monitoring and assessing students' spoken performance Photocopiable Tests for every Student's Book unit Teacher's DVD which shows the Elementary Student's Book material in action, plus author commentary